2020
DOI: 10.1038/s43016-020-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Local food crop production can fulfil demand for less than one-third of the population

Abstract: The distance between the origin and endpoint of food supply, and the 'localness' of food systems, are key considerations of many narratives associated with sustainability. Yet, information on the minimum distance to food crops is still scarce at the global level. Using an optimisation model based on 'foodsheds' (i.e. self-sufficient areas with internal dependencies), we calculate the potential minimum distance between food production and consumption for six crop types around the world. We show that only 11-28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 50 publications
0
88
0
1
Order By: Relevance
“…WFPs could also be central to efforts directed at empowering local market actors as well as reducing the distance between consumers and producers and the overreliance on globalized value chains. Although, recent research by Kinnunen et al [ 30 ] highlights the unfeasibility of localizing production for important global staples such as rice, maize and temperate cereals, there is increasing evidence that the local trade of minor crops, traditional varieties, and WFPs has potential to empower communities and increase livelihoods in rural areas, particularly of women and youth [ 31 , 32 ]. Meanwhile, the COVID-19 crisis has revealed the vulnerability of our global food systems to disease-related disruptions and shocks [ 33 , 34 , 35 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…WFPs could also be central to efforts directed at empowering local market actors as well as reducing the distance between consumers and producers and the overreliance on globalized value chains. Although, recent research by Kinnunen et al [ 30 ] highlights the unfeasibility of localizing production for important global staples such as rice, maize and temperate cereals, there is increasing evidence that the local trade of minor crops, traditional varieties, and WFPs has potential to empower communities and increase livelihoods in rural areas, particularly of women and youth [ 31 , 32 ]. Meanwhile, the COVID-19 crisis has revealed the vulnerability of our global food systems to disease-related disruptions and shocks [ 33 , 34 , 35 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…The sustainability of the food supply chain is certainly essential ( 34 ). Kinnunen et al showed that less than one-third of the world's population can meet their food demand within a 100-km radius ( 39 ). We should also change our view of food and diet which should no longer, or rather not only, considered an energy source but a reservoir of bioactive molecules beneficial to human health.…”
Section: Citizen Fortificationmentioning
confidence: 99%
“…According to official statistics [34], in the Comunidad de Madrid, the foods with the greatest weight in public procurement are: milk for drinking and dairy, meat, fruit, potatoes, and vegetables. In monetary terms, the highest expenditures, in descending order, are meat, fish, dairy products, and fresh fruits.…”
Section: Public Procurementmentioning
confidence: 99%